Implikasi Hukum Tata Negara Terhadap Peran Saniri Negeri dalam Pemerintahan Adat di Maluku Studi Pemerintahan Negeri Sameth: Penelitian - Reksi Giovani Amahoru; Fricean Tutuarima; Jurgen R Litualy (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine and analyze the meaning of Constitutional Law on the Role of Saniri Negeri in Customary Government in Maluku Study of Sameth State Government. Saniri negeri has functions, legal, obligations that must be carried out. As a representation of citizens in government, Saniri together with the government of the sameth state must pay attention to various problems that occur in the country. This study uses a qualitative descriptive research type (field research). The research subjects selected in this study include state government officials, members of Saniri Negeri and elements in the youth community and community leaders of the sameth state. Among others, saniri negeri 7-10 people. Data collection techniques are carried out through observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and data retrieval. The results of the study are that. The results of the study indicate a positive relationship and influence between saniri and the community, meaning that the role of saniri negeri in channeling community aspirations has a positive role in influencing the preparation of development programs in Negeri Sameth. Strengthening Saniri also includes bottom-up relations where Saniri can develop their capacity and empower themselves as actors of social reconstruction by inviting the widest possible community participation through all initiatives and decisions they make. The integration of research conducted aims to restore and develop the capacity of Saniri, both the capacity of their institutions and the capacity of their members. In addition, strengthening the capacity of Saniri members is also carried out through education and training, socialization, and technical guidance by synergizing with a community institution (Tifa Damai Maluku Institute) which already has long experience in providing assistance to the community in Negeri Sameth.